“Give voice” or “give ear” to subalternized people? The “Global South” in perspective in the work of Silvia Rivera Cusicanqui (Tempo e Argumento, 2024)
In recent years, in Brazil, the term “decolonial” has gained strength and support among intellectuals in the Social Sciences and Humanities, especially due to the work of the Modernity/Coloniality (M/C) group, which emerged in the 1990s and was formed by Latin Americans and Americanists. Before the emergence of M/C, however, a Bolivian sociologist and historian of Aymara origin, Silvia Rivera Cusicanqui, had already presented reflections and actions that, instead of decolonial, she prefers to call decolonizing/decolonizing. Despite more than 40 years of intellectual and political activity, especially in Andean libertarian movements, Rivera Cusicanqui is still little known in Brazilian academia. By reading and analyzing her works, as well as those of her interpreters, it is possible to uncover the originality of the proposals she put forward, always in a collective and collaborative manner. The aim of this article is to present, albeit partially, her thought-feeling-movement, showing the importance of theoretical-practical formulations for actions-reflections regarding the history of the present time in Latin America, particularly in Bolivia, her country of origin. Based on the work initially developed at the Taller de Historia Oral Andina (THOA), of which the intellectual-activist was one of the co-founders, it is possible to glimpse other ways of making-thinking the records of oral traditions, as well as their uses and possible abuses. Furthermore, the ch’ixi world advocated by her, notably in her latest works, allows us to combat “decolonial ventriloquism” (which seeks to speak for the subalternized), moving from discourses to practices that, in fact, impact the decolonization of knowledge and actions.
Keywords: Silvia Rivera Cusicanqui; Ch’ixi World; decolonial